The Concept of Sakinah Family in The Contemporary Muslim Generation - Fauzan, Ahmad; Amroni, Hadi (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research tries to reveal the meaning of the Sakinah family as one of the goals of marriage as described in the Al-Qur'an Surah Ar-Rum (30:21). The aim, in addition to gaining a clear understanding of the substantive meaning of the term, is to obtain concepts that can be applied in modern life. In achieving this goal, the researcher tries to examine a number of opinions of modern interpretive scholars and analyze them using a qualitative descriptive approach. Based on the results of the analysis of a number of ideas from modern commentators, it can be concluded that the Sakinah family is a family in which harmony, peace, and comfort are created, and runs on legal and religious norms. To realize a sakinah family, every prospective married couple needs to prepare for their marriage from an early age, especially those related to moral, material, mental and spiritual abilities, and have a strong commitment to shaping and maintaining family continuity based on the guidelines and rules of religion and society.